Control and Dynamic Simulation of Wire-Driven Precise Spray Robotic Arm. Issue 1 (1st July 2022) - Niu, Yuxin; Li, Yishu; Bao, Xiulan; Ma, Xiaojie; Xu, Kailun; Xu, Jiadong; Chen, Mingjun
Abstract: The spraying of citrus to kill insects is a necessary part of the citrus planting process. Most of the currently used sprayers are cover sprays, which cannot achieve accurate and low-consumption spraying. Causing a lot of pesticide waste and environmental pollution. Aiming at the difficulty of precise spraying of citrus leaves, this paper proposes a soft spraying manipulator with good bending characteristics and flexible operation ability. The robotic arm consists of 6 joints and 2 arm segments. The two arm segments of the robotic arm are driven by two wire ropes and move in two orthogonal planes respectively. The PD controller design is designed. The joint state observers are constructed to predict joint angles, angular velocities, and other information. The dynamic simulation experiment is carried out, and the relationship between the wire rope tension and the spring elastic force changes with time, and the relationship between each joint angle changes with time. These make the wire-driven precise spray robotic arm potentially useful in agricultural spraying.